(untitled) (Training and Practice : Journal of Educational Sciences, 2014)
Rostock modell didactics programme is based on an international cooperation. The programme aims to develop and investigate the elementary school student’s thinking. This study tests 1st-4th grader students. Its theoretical basis stands by constructive and cognitive pedagogical-psychological, metacognitive, emotional and conceptual change principles. It investigates the practical application of the theoretical concepts from the 1st to the 4th classes. I worked out the didactic plan of the experimental teaching of „Diet, lifestyle” and „Orientation” topics, using a Rostock Modell lesson plan based on a study of water, which is the basic model for the teaching ,ethod and we investigated students knowledge in these topics. According to the research the Rostock Modell didactics programme is an effective method to learn and understand science concepts on primary level.